(untitled) (Revista Apotheke, 2025)
The text reflects on the conceptions of Visual Arts teachers working in public schools in the municipality of Pelotas/RS, in relation to curricular practices using images and the links established with the themes of gender and sexuality. From a cross-section, we present data obtained from bibliographical reviews, the sending of images and semi-structured interviews. It emerged that Visual Arts teachers’ understanding of practices with images can reinforce and maintain prejudices and stereotypes in the school curriculum, but can also contribute to the process of deconstructing thoughts that standardize conduct and seek to fix identities. This is due to the teachers’ level of criticality, which includes their visual repertoire and the relationship established between images and the production of senses and meanings, considering their initial and continuing teacher training.